Descriptive Study of Knowledge Level of Hypertensive Disease in Adults in Neighborhood Pillars 14 Neighborhood Pillars 04 Wilayut Village - Puspitasari, Sentia; Dari, Tanty Wulan; Bahrudin, Moch; Fathimah Shifaza (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Hypertension is a condition where a person experiences an increase in blood pressure above normal, hypertension is often referred to as the silent killer because it is deadly without any symptoms as a warning to its victims. Low knowledge of health workers, patients, and the public about hypertension is the main cause of uncontrolled blood pressure. According to WHO data in 2021, it is estimated that 1.28 billion adults aged 30-79 years worldwide suffer from hypertension. According to data from Basic Health Research in 2018, it shows an increase in the prevalence of hypertension in Indonesia with a population of 260 million with a percentage of 34.1%. And at Puskemas Sukodono in 2022, the estimated number of people with hypertension aged 15 years and over is 2222. The incidence of hypertension is still quite high, so the author is interested in conducting a Descriptive Study of the Level of Knowledge of Hypertension in Adults in RT 14 RW 04 Wilayut Village. This study used a total sampling method approach. The study was conducted by giving questionnaires to samples that had been determined by the researcher. The level of knowledge of hypertension in Wilayut Village RT 14 RW 04 can be concluded from the characteristics of respondents according to an assessment score of 66.6% with 8 respondents getting good scores. and 33.3% with 4 respondents getting enough results. Lack of experience or information can affect a person's level of knowledge. To handle people who get sufficient result scores, local health workers such as puskesmas can carry out socialization or counseling using leaflets.